Identifikasi Kemampuan Berpikir Kritis Siswa SMP Pada Materi Hukum Newton - Rizal Khasani; Shofwan Ridho; Bambang Subali (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract: This study aims to determine the critical thinking skills of junior high school students in Newtons Law material. This research is included in descriptive research with a quantitative approach. The research subjects were 28 students III A SMP Negeri 4 Belik. Data instruments were written tests of 10 multiple choice questions to measure students' critical thinking skills. The results showed that the student test results were 14.29% (very low category), 57.14% (low category), 10.70% (medium category), 14.30% high category) and 3.57% (medium category). ) very high). While achieving indicators of critical thinking skills for indicators: providing basic explanations (62.50%), building abilities (55.40%), concluding (25.00%), making further explanations (35.70% ),  strategy and tactics (67.90%). Based on the results of the study it can be concluded that the critical thinking skills of class VIII A at SMP Negeri 4 Belik in Newtons law material are still low with an average score of 49.29.Key Words: Critical thinking ability; Newtons law